Relationship between motor function of the proximal stomach and transient lower oesophageal sphincter relaxation after morphine. Issue 9 (11th August 2004) - Penagini, R; Allocca, M; Cantù, P; Mangano, M; Savojardo, D; Carmagnola, S; Bianchi, P A
Abstract : Background: Morphine reduces the rate of transient lower oesophageal sphincter (LOS) relaxations but its site of action is presently unknown. There are no data available concerning its motor effects on the proximal stomach, an important site for triggering transient LOS relaxations. Aim: To evaluate the effect of morphine on the rate of transient LOS relaxations and motor function of the proximal stomach. Subjects and methods: In 19 healthy subjects, concurrent transient LOS relaxations with a sleeve sensor and motor function of the proximal stomach with a bag connected to an electronic barostat were recorded during pressure controlled (n = 9) and volume controlled (n = 10) gastric distensions after intravenous administration of placebo and morphine 100 μg/kg. Results: During pressure controlled distensions, intrabag volume was markedly decreased by morphine (median 189 ml (interquartile range 101–448) v 404 (265–868) after placebo; p<0.01) as was the rate of transient LOS relaxations (0.5/30 minutes (0.4–2) v 2.5 (2–4); p<0.01). When intrabag volume was kept constant (525 ml (490–600)) (that is, in volume controlled distensions), the rate of transient LOS relaxations was not affected by morphine (2/30 minutes (2–3) v 2.5 (2–3)). Gastric contractions decreased after morphine similarly during pressure controlled and volume controlled distensions (8.5/30 minutes (4–10) v 15.5 (9.5–20.5), p<0.02; and 6.5 (0–24) v 19.5 (12–22), p<0.05). Conclusions: The effect of morphine on transient LOS relaxations is dependent on the decrease in volume of the proximal stomach. Our data suggest that pharmacological interventions which decrease fundal volume should result in control of transient LOS relaxation mediated gastro-oesophageal reflux.